Challenges facing psychiatric intensive care during COVID-19. (1st September 2020) - Skelton, Luke; Blake, Lucy; Butler, Margaret; Pugh, Ria; Harries, Bethan; Sethi, Faisil
The coronavirus disease 2019 (COVID-19) pandemic has suddenly changed the landscape for psychiatric intensive care services, demanding a rapid transformation in the way that mental health care is delivered. This is the first of a series of articles describing the challenges facing psychiatric intensive care services during the evolving pandemic. Each article will focus on one of several unique challenges encountered during the pandemic, offering a timely account to share learnings. This article sets the scene for how COVID-19 might change psychiatric intensive care services.